Rethinking Student Belonging, Engagement, and Success: An Equity Perspective - Sarah O'Shea (JANZSSA)
The last weeks have seen a flurry of activity across the Australian university sector with the release of the _Universities Accord Final Report_. While I write, there is vigorous debate occurring, deliberating both the Accord’s strengths and its inherent limitations, one of the latter being the apparent perpetuation of low expectations for students with disability (see McLennan, 2024). Whilst the relative merits of some of the report’s recommendations have been questioned, there is little doubt that both this document—and the associated review process—have succeeded in placing educational equity at the centre of any future imaginings of the Australian higher education system. This is welcome news for many of us who have worked alongside students from more diverse backgrounds and witnessed the many obstacles encountered in their higher education journeys. To address these and other enduring issues, the Accord recommends significant changes that include accessible preparatory programs for future students, a better integrated tertiary system, and—of course—increases in student funding support. But I would argue there are other, far more fundamental, issues that also need to be addressed if we are to achieve the Accord’s ultimate goal of a “better and fairer education system”.